ПОВЕРХНОСТНЫЕ ХАРАКТЕРИСТИКИ КЛЕТОК КАК ОСНОВА ДЛЯ ИХ ИСПОЛЬЗОВАНИЯ В КАЧЕСТВЕ БИОСОРБЕНТОВ (Experimental biology, 2015)
The charge and chemical composition of the yeast cell surfaces Torulopsis kefir var kumis, strain 17 by methods of microelectrophoresis and infrared spectroscopy was studied. The mechanisms of interaction of metal ions with the cell surfaces have been established.
Keywords: microelectrophoresis; mechanism